The cruciform model of striate generation of the early VEP, re-illustrated, not revoked: A reply to Ales et al. (2013) - LALOR, EDMUND (My University, 2013)
Here we summarize the points raised in our dialog with Ales and colleagues on the cortical generators of the early visual evoked potential (VEP), and offer observations on the results of additional simulations that were run in response to our original comment. For small stimuli placed at locations in the upper and lower visual field for which the human VEP has been well characterized, simulated scalp projections of each of the visual areas V1, V2 and V3 invert in polarity. However, the empirically measured, earliest VEP component, “C1,” matches the simulated V1 generators in terms of polarity and topography, but not the simulated V2 and V3 generators. We thus conclude that, 1) consistent with the title of Ales et al. (2010a), polarity inversion on its own is not a sufficient criterion for inferring neuroelectric sources in primary visual cortex; but 2) inconsistent with additional claims made in Ales et al. (2010a), the simulated topographies provide additional evidence for – not against – the tenet that the C1 component is generated in V1.
PUBLISHED
Keywords: visual evoked potential (VEP)